Evaluation of the Coordinated Development of the “Population–Economy” in Counties Within the Beijing–Tianjin–Hebei Urban Agglomeration - Yanmin Ren; Yanyu Zhang; Shuhua Li; Yu Liu; Lan Yao; Linnan Tang (Land)
The coordinated development of urban agglomerations is a crucial means of establishing a territorial development and protection pattern with complementary advantages and high-quality development. In this study, an evaluation was performed on the coordinated development of the “population–economy” in the counties within the Beijing–Tianjin–Hebei urban agglomeration (BTHUA), focusing on the macro trend of coordinated development in this region. The evaluation methods included spatial autocorrelation analysis, the Gini coefficient, a comprehensive evaluation model, and a coupling coordination model. The results revealed that, in 2010 and 2022, the counties within the BTHUA exhibited strong positive spatial autocorrelation between evaluation indicators such as the population and economy, with notable and enhancing spatial clustering effects. The regional balance among all indicators was improved. The population distribution indicator and economic development indicator exhibited upward trends. The level of coupling coordination between the population and economy improved markedly. At the end of this paper, applicable strategies are recommended to drive economic growth and quality improvement in these counties, e.g., the orderly decentralization of the population and functions away from central urban areas to reduce the spatial carrying pressure and putting “policy guidance–fast-track resources–industrial upgrading” into practice. The purpose is to boost population–economy layout optimization and efficient resource allocation within the BTHUA.